Kajian Kandungan Gula dan Dampak Kesehatannya pada Produk Susu Cair, Minuman Susu, dan Minuman Mengandung Susu yang Terdaftar di Badan Pengawas Obat dan Makanan - Putri Damai Lestari; Diah Mulyawati Utari (Direktorat Politeknik Kesehatan Makassar, 2023)
Milk is the liquid secreted by female mammals such as cows, buffaloes, horses, goats, sheep and other milk-producing livestock. Indonesian FDA classifies milk into liquid milk, milk drinks and drinks containing milk. The level of milk consumption among Indonesian people is still lower than Vietnam and Malaysia. To increase milk intake, milk is added with flavors and sugar to make it more palatable. However, the added sugar content in milk causes significant contribution to daily carbohydrate and energy intake. This research aims to examine the nutritional content of sugar, lactose and sucrose in sterile milk products, namely liquid milk, milk drinks and milk-containing drink registered by Indonesia FDA. A total of 156 sterile milk products were taken as research samples and the total sugar, lactose and sucrose content as listed in the nutritional value information was assessed. Plain liquid milk has the lowest total sugar content (4.14 ± 0.91 g/100 ml), significantly different (p = 0.0005) compared to flavored milk (8.85 ± 1.35 g/100 ml), flavored milk drinks (9.04 ± 1.44 g/ 100 ml) and flavored milk-containing drinks (8.31 ± 0.97 g/100 ml). Lactose content of plain liquid milk (4.12 ± 1.32 g/100 ml), was significantly different (p = 0.0005) compared to flavored milk (3.85 ± 0.64 g/100 ml), flavored milk drinks (3.72 ± 1.05 g/100 ml) and flavored milk-containing drinks (3.09 ± 0.31 g/100 ml). sucrose content of plain liquid milk (0 g/100 ml) is significantly different because there is no addition of sucrose. Sucrose content of flavored milk (5.1 ± 1.14 g/100 ml), flavored milk drinks (5.23 ± 1.16 g/100 ml) and and flavored milk-containing drinks (4.93 ± 0.69 g/100 ml) were not significantly different (p=0.766). Due to the high intake of added sugars from flavored milk products, several policies need to be proposed to reduce added sugar intake, including the use of high-intensity sweeteners or product reformulation to reduce added sugar content.